0
$\begingroup$

Could someone explain to me why these two differ in value. Is it because of rounding and that it's a decimal number?

$(1.000218475^{23}- 1)*42731.41 + (1.000218475^{9}- 1)*42731.41 $ = 299.33

$(1.000218475^{32}- 1)*42731.41 $ = 299.75

Not sure what to tag, sorry.

$\endgroup$
0

1 Answer 1

1
$\begingroup$

You seem to expect that $a^b + a^c$ equals $a^{b+c}$. In general, it does not.

For example, $1^2 + 1^3 = 1+1=2$, but $1^{2+3}=1^5=1$.

$\endgroup$
2
  • $\begingroup$ Ahh yes you are correct, a^b*a^c = a^(b+c) $\endgroup$ Jun 10, 2015 at 15:59
  • $\begingroup$ @user3276954: Indeed $\endgroup$
    – MPW
    Jun 10, 2015 at 16:00

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .